Co-Production of Care Plans to Improve Safety on High-Dependency Rehabilitation Psychiatric Wards - Omer Malik; Angela Misra (BJPsych Open)
Aims: Care plans are the cornerstone of Rehabilitation Psychiatry. These were not being completed collaboratively with patients during monthly ward rounds, leading to impaired communication, lack of patient involvement in risk reduction strategies, and frustration. This contributed to volatility and increased risk incidents.